Condition assessment of power transformer bushing using SFRA and DGA as auxiliary tools - Mohseni, B.; Hashemnia, N.; Islam, Syed (2016)
Dielectric insulation of a transformer bushing deteriorates as a function of temperature, oxidation, and moisture. This causes accelerated aging of oil and cellulosic solid insulation, generating fault gases within bushing oil and eventual permanent failure. To prevent such failures, effective analyses and diagnoses need to be investigated. Dissolved Gas Analysis (DGA) can give the indication of internal abnormalities inside the transformer bushing. In addition, Frequency response analysis (FRA) is a widely accepted tool for mechanical deformation diagnosis within power transformers. Although a large number of studies have been conducted on the detection of transformer winding deformation by FRA technique, the impact of bushing faults on the transformer FRA signature has not been sufficiently investigated. It is the goal of this paper to propose precise simulation as well as practical analyses demonstrating the impact of bushing faults on the FRA signature. A real transformer bushing geometry is modelled through 3D finite element analysis (FEM) on which different bushing faults are emulated. To verify the derived simulation results, DGA of transformer oil as well as FRA are performed on a three-phase, 132 kV, 315 MVA power transformer. It can be observed clearly from the results, that bushing faults have an impact on the FRA signature and DGA of the power transformer.